Maternal Perinatal and Concurrent Anxiety and Mental Health Problems in Early Childhood: A Sibling‐Comparison Study. Issue 2 (11th December 2018) - Gjerde, Line C.; Eilertsen, Espen M.; Eley, Thalia C.; McAdams, Tom A.; Reichborn‐Kjennerud, Ted; Røysamb, Espen; Ystrom, Eivind
Abstract : Do associations between maternal anxiety symptoms and offspring mental health remain after comparing differentially exposed siblings? Participants were 17, 724 offspring siblings and 11, 553 mothers from the Norwegian Mother and Child Cohort study. Mothers reported anxiety and depressive symptoms at 30 weeks' gestation, and 0.5, 1.5, 3, and 5 years postpartum. Child internalizing and externalizing problems were assessed at ages 1.5, 3, and 5, and modeled using multilevel analyses with repeated measures nested within siblings, nested within mothers. Maternal pre‐ and postnatal anxiety were no longer associated with child internalizing or externalizing problems after adjusting for maternal depression and familial confounding. Maternal anxiety when the children were in preschool age, however, remained significantly associated with child internalizing but not externalizing problems.